A combination of spray-dried porcine plasma and spray-dried blood meal optimizes starter pig performance - L J Kats; J L Laurin; Michael D Tokach; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1992)
A total of 298 weanling pigs (initially 12.11b and 19 d of age) was used in a 25-(SDPP) and spray-dried blood meal (SDBM) in a high nutrient density diet on starter pig performance. Pigs were allotted by weight to eight replicates of five treatments with seven to eight pigs per pen. Pigs were assigned to one of five dietary treatments with 0, 25, 50, 75, or 100% of the SDPP replaced with SDBM on an equal lysine basis. Therefore, diets contained 10, 7.5,5.0, 2.5, or 0% SDPP combined with 0, 1.63, 3.25, 4.8, or 6.5% SDBM, respectively. All phase I diets were formulated to contain 20% dried whey, 1.50% lysine, .81% isoleucine, and .37% methionine. These diets were fed from d 0 to 14 postweaning. On d 14, all pigs were switched to a common phase II diet containing 10% dried whey and 2.5% SDBM and was formulated to 1.25% lysine. Pigs were fed this diet for the remainder of the trial (d 14 to 25 postweaning). A quadratic response occurred for average daily gain and feed efficiency during phase I, with pigs fed a combination of spray-dried porcine plasma and spray-dried blood meal having superior performance compared to pigs fed diets containing only spray-dried plasma or spray-dried blood. Maximum performance was seen with the combination of 7.5% spray-dried porcine plasma and 1.63% spray-dried blood meal. Therefore, the results of this trial show that phase I diet cost can be reduced and performance improved by formulating the diet with a combination of spray-dried porcine plasma and spray-dried blood meal rather than spray-dried plasma alone.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Starter; Porcine plasma; Blood meal